Blockchain for Environmental Governance: Can Smart Contracts Reinforce Payments for Ecosystem Services in Namibia? - Oberhauser, Daniel (Frontiers in Blockchain, 2019)
The Global South harbors some of the planet’s most precious natural resources and is hence key in addressing the pressing environmental challenges of the Anthropocene. Here, payments for ecosystem services (PES) have recently gained importance as a means of environmental governance, increasingly complementing conventional command-and-control approaches. For instance, climate change is now mitigated through carbon offset payments and biodiversity loss is addressed through wildlife conservation performance payments. However, such payment schemes in the Global South face numerous challenges as identified by a large body of literature. This paper investigates if blockchain technology can help address some of the challenges by reinforcing PES programs with tamper-proof blockchain smart contracts. To this end, the paper presents a proof-of-concept of a blockchain-based wildlife conservation performance payments scheme in Namibia: the habitat integrity of an elephant corridor is assessed by remote sensing algorithms, which in turn trigger fictitious blockchain smart contract payments to surrounding communities. The application allows to practically discuss the potential of blockchain technology regarding three key aspects of PES: (i) effectiveness (conditionality) of environmental monitoring (ii) efficiency and transaction costs, as well as (iii) equity and benefit distribution. The case presented here is an example for linking the digital Blockchain sphere to practical challenges of natural resource management in the physical world. As such, it illustrates some potentials of the technology, but also shows how Blockchain technology is unlikely to provide transformative solutions in geographies with complex environmental governance.